Complete plastome sequence of Ardisia bullata G. H. Huang & G. Hao, an endemic species in Hainan. Issue 3 (2nd July 2020) - Wang, Huan-Xin; Ke, Xin-Ru; Wang, Rui-Xuan; Wang, Hong-Xin; Zhao, Hong-Liang
Abstract: Ardisia bullata G. H. Huang & G. Hao is a small shrubs of Primulaceae. It is only distributed in Hainan provinces of China. It is a plant medicinal value. There is no study on the genome of A. bullata so far. Here, we report and characterize the complete plastid genome sequence of A. bullata in an order to provide genomic resources useful for promoting its conservation. The complete chloroplast genome of A. bullata is 160, 176 bp in length with a typical quadripartite structure, consisting of a large single-copy region (LSC, 89, 710 bp), a single-copy region (SSC, 18, 357 bp), and a pair of inverted repeats (IRs, 26, 054 bp). There are 133 genes annotated, including 83 unique protein-coding genes, eight unique ribosomal RNA genes, and 37 transfer RNA genes. The overall G/C content in the plastome of A. bullata is 36.0%. The complete plastome sequence of A. bullata will provide a useful resource for the conservation genetics of this species as well as for phylogenetic studies in Apocynaceae.